2009
DOI: 10.1002/ase.82
|View full text |Cite
|
Sign up to set email alerts
|

Secondary school science predictors of academic performance in university bioscience subjects

Abstract: In 2009 the Faculty of Health Sciences at La Trobe University in Melbourne, Australia is introducing a common first year for 11 different undergraduate courses in the faculty. Current prerequisite science entry requirements vary with course and range from none to at least two science or mathematics subjects and from approximately 50 to 99 in Equivalent National Tertiary Entrance Rank (ENTER) scores. Under the previous structure, students in different courses completed a variety of different subjects at first y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…While a previous background in physics or chemistry would not be intuitive in an anatomy and physiology unit, both predictors combined increase BMS100 grade by approximately 13%. This data supports a similar finding at La Trobe University, where high school chemistry and physics were seen to be associated with higher academic performance in several anatomy and physiology units (Green et al, 2009). The number of students entering university with higher level or intermediate mathematics, chemistry and physics is declining in Australia (Barrington, 2006;Rubinstein, 2009), which establishes an ongoing need for supporting this body of students as a collective.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…While a previous background in physics or chemistry would not be intuitive in an anatomy and physiology unit, both predictors combined increase BMS100 grade by approximately 13%. This data supports a similar finding at La Trobe University, where high school chemistry and physics were seen to be associated with higher academic performance in several anatomy and physiology units (Green et al, 2009). The number of students entering university with higher level or intermediate mathematics, chemistry and physics is declining in Australia (Barrington, 2006;Rubinstein, 2009), which establishes an ongoing need for supporting this body of students as a collective.…”
Section: Discussionsupporting
confidence: 88%
“…Subjects studied in secondary school have previously shown to be associated with success in health science units at another Australian university (Green, Brown, & Ward, 2009). In our study, significant increases in the average BMS100 grade were observed in all three cohorts when students studied mathematics at a year 12 level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010 and 2011, roughly 30% of students failed first-year physiology. As has previously been reported, success in physiology is directly correlated to tertiary entrance rank (12). Since there is no senior high school science requirement for entry into the nursing degree and given the low tertiary entrance criteria, it is not surprising that large numbers of nursing students fail first-year physiology.…”
mentioning
confidence: 86%
“…Indeed, feelings of incompetence and inadequate preparation are major reasons for nursing students discontinuing their nursing studies at universities (1,8). Studies have consistently shown that success in first-year undergraduate human biosciences is strongly correlated with prior experience in chemistry and biology as well as overall high school achievement (8,12,18,27,30). Thus, it is remarkable that direct entry from secondary school into Bachelor of Nursing programs do not require some form of general science prerequisite.…”
mentioning
confidence: 93%